Ecological interactions involving plant selenium hyperaccumulation - Quinn, Colin Francis, author; Pilon-Smits, Elizabeth, advisor; Paschke, Mark, committee member; Seshadri, Arathi, committee member; Steingraeber, David, committee member (Colorado State University. Libraries, 2010)
To view the abstract, please see the full text of the document.
Covers not scanned.
Keywords: Hyperaccumulator plants; Plants -- Effect of selenium on; Selenium -- Environmental aspects